2008
DOI: 10.1097/wno.0b013e318167549f
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Anti-Retinal Antibodies in Normal Human Serum

Abstract: The presence of anti-retinal antibodies is observed in a majority of normal control human sera, suggesting that identification of new candidate retinal autoantigens should be cautiously interpreted and subject to rigorous testing for disease association. Additional studies will aid development of a standardized protocol for validation of potential pathogenic seroreactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 27 publications
1
48
0
2
Order By: Relevance
“…Masking of laboratory personnel to patient diagnosis has not been consistently reported. Different labs have varied in the species origin of the retinal protein extracts, the methods of protein extraction and their definition of positive reactivity [30]. Studies have frequently used bovine, rodent and monkey tissue in assays on account of the difficulty of obtaining fresh cadaveric human retinal tissue samples.…”
Section: Specialized Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Masking of laboratory personnel to patient diagnosis has not been consistently reported. Different labs have varied in the species origin of the retinal protein extracts, the methods of protein extraction and their definition of positive reactivity [30]. Studies have frequently used bovine, rodent and monkey tissue in assays on account of the difficulty of obtaining fresh cadaveric human retinal tissue samples.…”
Section: Specialized Investigationmentioning
confidence: 99%
“…A recent study on 92 samples of laboratory ‘normal control’ human sera revealed that 62% of serum samples had antiretinal IgG immunoreactivity to solubilized human retinal proteins [30]. Western blot analysis detected reactivity against a few retinal protein bands in 33%, and against 5 or more retinal protein bands in 22%, ranging in weight from 13 to 148 kDa [30]. Autoantibodies have been found in numerous other retinal and systemic diseases, and in patients with cancer but no visual symptoms [50,51].…”
Section: Antigens and Antibodiesmentioning
confidence: 99%
“…Although we performed WB analysis against one of the possible candidate photoreceptor-specific proteins, beta-3 subunit of guanine nucleotide protein [8], positive immunoreactivity was not found (data not shown). Thus, we must consider that this possible antibody developed during the course of the disease process, or developed independently [9]. Further investigations, including the identification of these retinaspecific antigens by mass spectrometry, are needed to characterize the antibodies associated with slowly progressive AIR.…”
Section: Commentsmentioning
confidence: 97%
“…However, the pathogenicity of other retinal autoantibodies has not been so well studied. Using Western blot techniques, Shimazaki et al 32 have shown that 33% of normal human serum demonstrates 1 to 2 bands, and 22% of normal human serum contains ≥5 bands. Given the numerous putative retinal autoantibodies that have been described, and the fact that normal serum can have significant antiretinal antibody activity, it is of paramount importance to definitively prove the pathogenicity of the autoantibodies suspected of causing AIR.…”
Section: Antiretinal Antibodies: Pathogenic Uncertaintiesmentioning
confidence: 99%